Case report: Innovative treatment for one metastatic thyroid-like follicular carcinoma of the kidney with ATM and POLE mutations - Lei, Jin-Ju; Rao, Jie; Feng, Hong-Yan; Cao, De-Dong; Yan, Hong-Lin; Yuan, Jing-Ping; Jiang, Zhen-Min; Zhang, Yi-Qiao (Frontiers in Oncology, 2024)
Thyroid-like follicular renal cell carcinoma (TLFRCC), also known as thyroid-like follicular carcinoma of the kidney or thyroid follicular carcinoma like renal tumor, is an exceedingly rare variant of renal cell carcinoma that has only recently been acknowledged. This neoplasm exhibits a distinct follicular morphology resembling that of the thyroid gland. Immunohistochemical analysis reveals positive expression of PAX8, Vimentin, and EMA, while thyroid-specific markers TG and TTF1 are consistently absent. Furthermore, there is a notable absence of any concurrent thyroid pathology on clinical evaluation. Previous reports have suggested that TLFRCC is an indolent, slow-growing malignancy with infrequent metastatic potential. In this report, we present a case of TLFRCC characterized by remarkable ossification and widespread metastasis, including multifocal pulmonary lesions, involvement of the abdominal wall, and infiltration into the psoas muscle. To our knowledge, this represents only the third documented instance of distant metastasis in thyroid follicular renal carcinoma. The current case demonstrates a therapeutic approach that combines radiotherapy with the utilization of toripalimab, a programmed cell death 1 (PD-1) receptor inhibitor, and pazopanib. This treatment regimen was tailored based on comprehensive genomic profiling, which identified mutations in the POLE (catalytic subunit of DNA polymerase epsilon) and ATM (ataxia-telangiectasia mutated) genes, both of which have been implicated in the pathogenesis of various malignant tumors. These findings represent a novel discovery, as such mutations have never been reported in association with TLFRCC. Thus far, this therapeutic approach has proven to be the most efficacious option for treating metastatic TLFRCC among previously reported , and it also marks the first mention of the potential benefits of radiotherapy in managing this particular subtype of renal cell carcinoma.